2014
DOI: 10.1007/s12665-014-3516-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prescribed fire on surface soil in a Pinus pinaster plantation, northern Portugal

Abstract: In order to decrease the risk of severe wildfire, prescribed fire has recently been adopted in Portugal and elsewhere in the Mediterranean as a major tool for reducing the fuel load instead of manual or mechanical removal of vegetation. There has been some research into its impact on soils in shrublands and grasslands, but to date little research has been conducted in forested areas in the region. As a result, the impact of prescribed fire on the physico-chemical soil characteristics of forest soils has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 22 publications
7
5
0
Order By: Relevance
“…Our results are consistent with former research showing that repeated PB in a P. halepensis plantation in Southern Italy had only short-term or no effects on chemical and microbial properties of the fermentation layer and the 5 cm soil layer underneath, with a superimposed predominance of the water factor [31]. Likewise, no or minimal effects of PB on soil physical and chemical properties were observed in a short-grass plain in Texas [37], a P. pinaster plantation in Portugal [68] and a P. palustris forest in South Caroline [69].…”
Section: Effect Of Pb On Soil Microbial Communitysupporting
confidence: 93%
“…Our results are consistent with former research showing that repeated PB in a P. halepensis plantation in Southern Italy had only short-term or no effects on chemical and microbial properties of the fermentation layer and the 5 cm soil layer underneath, with a superimposed predominance of the water factor [31]. Likewise, no or minimal effects of PB on soil physical and chemical properties were observed in a short-grass plain in Texas [37], a P. pinaster plantation in Portugal [68] and a P. palustris forest in South Caroline [69].…”
Section: Effect Of Pb On Soil Microbial Communitysupporting
confidence: 93%
“…The direct and indirect effects of fire were often studied in soil surface (e.g., Arocena and Opio, 2003;Huseyin, 2006;Thomaz and Fachin, 2014;Meira-Castro et al, 2015;Armas-Herrera et al, 2016;Aznar et al, 2016), but some works showed that these effects reach deeper soil layers, at least down to 30 cm (Fonseca et al, 2011;Dennis et al, 2013;Heydari et al, 2017). The present work is in agreement with the results presented by the former authors, contributing to reinforce the idea that more attention should be given to the direct and indirect effects of fire at deeper depths.…”
Section: Depthsupporting
confidence: 91%
“…The importance of organic carbon on physical, chemical and biological soil properties is well documented (Granged et al, 2011a;Meira-Castro et al, 2014). In this study the results indicate that repeated annual burning cause a decline in soil C (Table 1) when compared to relatively infrequent burning (biennial, triennial and quadrennial).…”
Section: Resultssupporting
confidence: 57%